Zur Rolle der Terminativitaet / Aterminativitaet (T/AT) im Aspekt- und Aspektbildungssystem der russischen Sprache der Gegenwart Ein Beitrag zur Theorie der Aspektualitaet - Schlegel, Hans (Specimina philologiae Slavicae, 1999)
The intention of the author was (...) to prove that the terminativity / aterminativity - as a "covert" category - is the semantic basis and generator of the Russian verbal aspect, thus de facto controlling the whole mechanism of the Russian aspect system - education , Meaning and use of the aspect. In order to largely objectify the profound semantic analysis required for this, we have decomposed the most general semantic properties of the verbs and the aspectual context into differential semantic features and arranged them in algorithmic form. Thus, we were able to follow the interaction of the general meanings of the aspect with the T / AT through the linguistic subsystems of aspect formation and the special aspect meanings. This algorithmic analysis as the main method of our investigation has u.E. In a convincing way many previously contentious questions have been solved, and common views have been confirmed or refuted.